Persistent alterations of cortical hemodynamic response in asymptomatic concussed patients - Allyssa K Memmini; Xin Sun; Xiaosu Hu; Jessica Kim; Noelle K Herzog; Mohammed N Islam; Daniel H Weissman; Alexander J Rogers; Ioulia Kovelman; Steven P Broglio (Concussion)
Aim: The underlying neurophysiological effects of concussion often result in attenuated cognitive and cortical function. To understand the relation between cognition and brain injury, we investigat...